A Prospective Study of Clinical Profile of Acute Appendicitis & Its Correlation with Ultrasonography Findings In Patients Admitted In J.A. Group of Hospitals, Gwalior (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Acute appendicitis remains one of the most common causes of acute abdomen requiring emergency surgical intervention. Despite classical signs and symptoms, its variable presentation can complicate diagnosis, leading to delayed treatment and serious complications. Ultrasonography (USG), being radiation-free, cost-effective, and readily available, plays a pivotal role in the diagnostic workup, especially in settings with limited access to advanced imaging.Aim & Objective: To study the clinical profile of patients with acute appendicitis and correlate clinical features with ultrasonographic findings to improve diagnostic precision and surgical outcomes.Materials & Methods: This prospective observational study was conducted over 18 months in the Department of General Surgery, J.A. Group of Hospitals, Gwalior, involving 89 patients aged 16–60 years with a provisional diagnosis of acute appendicitis. Detailed clinical history, physical examination, and ultrasonographic evaluations were performed. Diagnosis was confirmed intraoperatively. Data was analyzed for demographic distribution, clinical features, USG parameters, and outcomes.Results: Most patients were males (67.41%) aged between 21–30 years. All presented with central abdominal pain migrating to the right iliac fossa. McBurney’s point tenderness and rebound tenderness were noted in 100% of cases. Ultrasonographically, probe tenderness was present in 97.75%, and the mean appendiceal diameter was 7.43 ± 0.98 mm. All cases showed concordance between clinical, USG, and intraoperative diagnosis. There were no complications or mortality, and all patients had a full recovery.Conclusion: This study demonstrated a strong correlation between clinical signs and ultrasonographic findings in acute appendicitis. Combining both modalities improves diagnostic accuracy, enables timely surgical intervention, and reduces the risk of negative appendectomy and associated complications.